PENGARUH HARGA, LOKASI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN RUMAH PADA CV. MEDAN PROPERTI - Tumanggor, Mutawaqil Bilah; Samosir, Suhaila Husna; Satria, Dimas (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2023)
The purpose of this study is to comprehend how CV. Medan Properti in Medan implements and weighs the impact of many aspects, including location, cost, and lifestyle, on decisions about which homes to buy. The study uses a questionnaire survey design and a quantitative methodology. The study's participants include 90 responders who are interested in buying a home, including Medan Properti, the research object, and CV. The research makes use of quantitative techniques, such as documentation, questionnaires, and observation. Validity, reliability testing, classical assumptions, and multiple linear regression analysis utilizing SPSS 25 software are examples of data analysis methodologies. The t-test results show that lifestyle, location, and price all positively and significantly affect consumers' decisions to buy. According to the F-test results, homebuyers at CV. Medan Properti in Medan are significantly influenced by price, location, and lifestyle taken together.